Theoretical studies of optically induced high spin polarization and cubic anisotropy in cubic semiconductors - M. Idrish Miah (Department of Physics, Sebelas Maret University, 2025)
Theoretical studies of optical spin polarization and cubic anisotropy in cubic semiconductors GaAs and GaSb are performed. We use Kane wave functions to calculate the eight-level transition matrix elements permitted by the optical selection rules. It is found that the spin polarization depends on semiconductor, the pumping direction as well as the photon energy. A high spin polarization of about 55% is obtained for GaSb. The anisotropic effect in these cubic crystals is clearly seen. The band edge polarization is found to be flatter and higher for GaAs than that for GaSb. The results are discussed in comparison with the experimental data available in the literature.